O sujeito adolescente, o ato infracional e a família: considerações psicanalíticas sobre as voltas para casa - Teixeira, Giovana Leão Caixeta (2019)
The objective of this research was to analyze the repetition of the infraction act as one of family dynamics operator. This study analyzes the familiar plot marked by violence and institutionalizations. The family plot is understood as the entanglement of subjects who establish links between themselves marked by ambivalences and affective excesses of unconscious orders. Methodologically, the research was supported by psychoanalytical precepts and used case construction as a strategy for analysis. Interviews were conducted with Henrique, an 18-year-old boy, internd for the seventh time in an institution of socio-educational measures. Other interviews were conducted with him, as soon as he was deinstitutionalized, at a University Psychology Clinic. The father, the mother and the stepfather were interviewed in their places of work or during a home visit. The interpretations on the case point out how the house-family became a place of passage, while the house-institution remained as the only shelter for Henrique, although precarious. The characters in the family plot are also marked by institutional excesses: the father was imprisoned for attempted murder, the older brother is imprisoned for involvement in trafficking, the mother has lost custody of all her children (as judged by control institutions). The possible interpretations are outlined gradually with notes to the intrinsic relation between the processes of subjectivation and the institutionalization rooted in the molds of civilizational training of the subjects. The case signals the fragility of the service provided to adolescents in conflict with the law, which, when they reach the age of majority, has no definite destination, since no possibility of life outside the cloister had been built, thus becoming radically helpless. Finally, psychoanalytic productions dealing with the management of situations of social helpless were presented as ways of thinking about the potentialities of resistance assumed by psychoanalysis in face of clinic of the act.